(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Bhabani Bhattacharya can’t be rejected as a minor essayist regardless. He is positively one of the significant scholarly powers who have contributed in extraordinary measure to the improvement of Indian fiction in English. An observer to pre and post free India, in the same way as other of his peers he could get his nation’s otherworldly anguish, its difficulties, it desires it inconsistencies, its nerves, its disappointment and expectations. Specifically his anecdotal yield doesn’t profess to have broken new grounds, in any case, in fact, he can be said to have built up for himself a pride of spot in Indian writing.